2008
DOI: 10.1002/art.23579
|View full text |Cite
|
Sign up to set email alerts
|

Safety and usefulness of minor salivary gland biopsy: Retrospective analysis of 502 procedures performed at a single center

Abstract: Objective. To analyze the safety of our biopsy technique and the effectiveness of minor salivary gland biopsy (MSGB) for the diagnosis of Sjö gren's syndrome (SS) and amyloidosis. Methods. We conducted a retrospective analysis of 452 patients with suspected SS and 50 with suspected amyloidosis and negative periumbilical fat aspiration analysis who underwent MSGB at a single center. Diagnostic evaluation for SS included Schirmer's test, unstimulated whole salivary flow, detection of antinuclear antibodies and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 34 publications
(47 reference statements)
2
75
1
6
Order By: Relevance
“…Although the tongue is the most common oral site [6,10,[30][31][32], cases of amyloid deposition in the palate [11,33,34], maxillary vestibule [35], gingival [9] and floor of the mouth [36] have been mentioned as well. Rarely, minor or major salivary glands infiltration and related hypofuctionxerostomia can be seen [37][38][39]. Noteworthy, oral involvement is extremely rare as the localized solitary manifestation of amyloidosis, but when present the tongue is primarily affected [6,[8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Although the tongue is the most common oral site [6,10,[30][31][32], cases of amyloid deposition in the palate [11,33,34], maxillary vestibule [35], gingival [9] and floor of the mouth [36] have been mentioned as well. Rarely, minor or major salivary glands infiltration and related hypofuctionxerostomia can be seen [37][38][39]. Noteworthy, oral involvement is extremely rare as the localized solitary manifestation of amyloidosis, but when present the tongue is primarily affected [6,[8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…SS is a significant disease that is more commonly seen in females (F/m: 9/1) and in the 4th and 5th decades (4,9,11,13). Females made up 93% of the cases in our study and the mean age was 53 years.…”
Section: Resultsmentioning
confidence: 62%
“…Caporali et al found the ratio of biopsies with at least one lymphoid focus to be 24.5% in their study including 435 patients (11). The ratio of the biopsies with a focus score of ≥ 1 was found to be 42.7% among 120 biopsies in another study conducted by morbini et al (12).…”
Section: Resultsmentioning
confidence: 85%
“…Minor salivary gland biopsy: The minor salivary gland biopsy is a simple procedure carried out by a dentist, which now is widely used in internal medicine and rheumatology for the diagnosis of SS 40 and other infiltrative diseases of connective tissue, such as amyloidosis, hemochromatosis, and sarcoidosis 41 . Although it is a simple procedure, some side effects and disadvantages of this diagnostic technique have been reported, such as pain, salivary duct trauma 14 , infection, loss of sensation and development of granulomas 42 .…”
Section: Diagnosismentioning
confidence: 99%